Extraction and Qualitative Analysis of Floral Volatiles of Alstonia scholaris - cruza, Kevin J. D; Ambatkar, Mugdha V (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The strong fragrance of the flowers of Alstonia scholaris indicates the presence of volatile compounds.The pharmacological properties of the flowers of A. scholaris have been explored to a lesser extentthan those of the bark and leaves. In the present study, the floral volatiles were extracted by steamdistillation, and the major components were identified using GC–MS analysis. The cooling system inthe distillation set-up was modified to significantly reduce the wastage of water. The distillatecontained terpenes, such as eucalyptol (1,8-cineole) and linalool, which have well establishedmedicinal properties. The present study qualitatively identified those volatiles that can be extractedfrom the flowers by through steam distillation, without the use of an organic solvent. The studyexplores the potential of the flowers of A. scholaris as a source of fragrant compounds withbiologically activity.